Identification of Usability Issues of Interactive Technologies in Cultural Heritage through Heuristic Evaluations and Usability Surveys - Duyen Lam; Thuong Hoang; Atul Sajjanhar (Multimodal Technologies and Interaction, 2021)
Usability is a principal aspect of the system development process to improve and augment system facilities and meet users’ needs and necessities in all domains. It is no exception for cultural heritage. Usability problems of the interactive technology practice in cultural heritage museums should be recognized thoroughly from the viewpoints of experts and users. This paper reports on a two-phase empirical study to identify the usability problems in audio guides and websites of cultural heritage museums in Vietnam, as a developing country, and Australia, as a developed country. In phase one, five-user experience experts identified usability problems using the set of usability heuristics, and proposed suggestions to mitigate these issues. Ten usability heuristics identified a total of 176 problems for audio guides and websites. In phase two, we conducted field usability surveys to collect the real users’ opinions to detect the usability issues and examine the negative-ranked usability. The outstanding issues for audio guides and websites were pointed out. Identification of relevant usability issues and users’ and experts’ suggestions for these technologies should be given immediate attention to helping organizations and interactive service providers improve technologies’ adoptions. The paper’s findings are reliable inputs for our future study about the preeminent UX framework for interactive technology in the CH domain.